Epstein–Barr virus reactivation in pediatric allogeneic stem cell transplant recipients: an 11-year experience on viral load and B lymphocyte monitoring strategy - Ferrando, Giulia; Bagnasco, Francesca; Pierri, Filomena; Pestarino, Sara; Dell’Orso, Gianluca; Giardino, Stefano; Di Marco, Eddi; Santaniello, Maria; Castagnola, Elio; Faraci, Maura (Frontiers in Immunology, 2024)
Background Epstein–Barr virus (EBV) reactivation represents a frequent condition after allogeneic hematopoietic stem cell transplantation (allo-HCT) and can cause the development of a severe complication: post-transplant lymphoproliferative disease (PTLD). This retrospective study aims at investigating the incidence of EBV reactivations and analyzing the potential impact of recipient/donor-related transplant-related factors in pediatric patients. The secondary objective was to study the consequences of the approach used at our center regarding the initiation of pre-emptive therapy. Methods This study used a retrospective evaluation of patients aged ≤25 years who received an allo-HCT at IRCCS (Istituto di Ricovero e Cura a Carattere Scientifico) Istituto Giannina Gaslini, between 2012 and 2022, with follow-up censored in July 2023. Criteria to start rituximab were as follows: a viral load ≥20,000 copies/105 PBMCs or ≥10,000/105 PBMCs associated with a rise in the proportion of CD 20+ lymphocytes. Results Overall, 214 allo-HCTs were performed in 189 patients. A total of 127 (59.3%) procedures were complicated by at least one EBV reactivation, but in only one rituximab was administered. All other reactivations were characterized by viremia below reference ranges and no increase in CD20+ lymphocytes, without clinical consequences. Risk factors for EBV reactivation identified were associated with delayed immune reconstitution. Conclusion These results could suggest the effectiveness of the approach used in providing pre-emptive therapy. The strategy adopted differs from that highlighted by other studies and allowed the reduction of the number of children who received rituximab. It has proven effective considering the low incidence rate of PTLD and reduces the risk of rituximab-related adverse events.